2010
DOI: 10.1108/13665621011040680
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leadership style on team learning

Abstract: PurposeThis paper seeks to explore the effect of leadership style of a team leader on team‐member learning in organizations, to conceptually extend an initial model of leadership and to empirically examine the new model of ambidextrous leadership in a team context.Design/methodology/approachQualitative research utilizing the case study method is used for empirical validation.FindingsThe leadership style (transformational, transactional, or ambidextrous) adopted by the team leader has an operational effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 45 publications
7
79
0
3
Order By: Relevance
“…This finding aligns with Bucic et al (2010) and Mebane and Galassi (2003) who found that both vertical leadership styles were related to university teacher team learning. Our data further specify this by suggesting that leaders in integrative team types were aware of the process but did not actively interfere.…”
Section: Vertical Team Leadership Behaviors From a Distancesupporting
confidence: 74%
See 2 more Smart Citations
“…This finding aligns with Bucic et al (2010) and Mebane and Galassi (2003) who found that both vertical leadership styles were related to university teacher team learning. Our data further specify this by suggesting that leaders in integrative team types were aware of the process but did not actively interfere.…”
Section: Vertical Team Leadership Behaviors From a Distancesupporting
confidence: 74%
“…On the other hand, Timperley et al (2007) stressed that vertical transactional leadership behaviors are also promising for structuring collaborative teacher learning in (secondary) education. Bucic et al (2010) and Mebane and Galassi (2003) demonstrated that both vertical transformational and transactional leadership styles encouraged university teacher team learning by challenging teachers to share and by structuring the task. The reviews of London (2014) and Nicolaides et al (2014) suggest that the most effective leadership style depends on the team's situation, such as the task features or perceived task features, but supporting evidence is limited.…”
Section: The Role Of Team Leadership Behavior In Supporting Universitmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning within teams has been seen as particularly important by a number of researchers, including Senge (1990, 10) Zellmer-Bruhn and Gibson 2006), but it is more common to define it in terms of processes (e.g. Boak 2014;Bucic, Robinson, and Ramburuth 2010;Fisser and Browaeys 2010;Gibson and Vermeulen 2003;Savelsbergh, van der Heijden, and Poell 2010;Timmermans et al 2011). For example, Edmondson (2002, 129) defines team learning as 'a process in which a team takes action, obtains and reflects upon feedback, and makes changes to adapt or improve'.…”
Section: Team Learning Action Research and Action Learningmentioning
confidence: 99%
“…However, managers' leadership styles can influence how employees respond, as is shown by previous research that indicates that a manager's leadership style can foster team learning (e.g. Bucic, Robinson, & Ramburuth, 2010; Koeslag-Kreunen, Van der Klink, Van den Bossche, & Gijselaers, 2017;Raes et al, 2013). Therefore, to explain the relationship between VET colleges' supportive context and teachers' team learning, not only how team leaders implement team-oriented HRM should be taken into account, but also how they act as leaders.…”
Section: Fostering Vet Teachers' Team Learning: a Focus On Team-orienmentioning
confidence: 99%